Clinical Subtypes and vHIT Parameters in a Population With Bilateral Vestibulopathy - Mancino-Moreira, Fiorella; Rueda, Almudena; Esteban-Sanchez, Jonathan; Martin-Sanz, Eduardo (Frontiers in Neurology, 2021)
Objective: To evaluate the different peripheral, neurological, genetic, and systemic etiologies of bilateral vestibulopathy (BVP) and the value of vHIT in the diagnostic process. Materials and methods: A retrospective case review was performed on 176 patients diagnosed with BVP in a tertiary referral center, between 2010 and 2020. Inclusion criteria comprised imbalance and/or oscillopsia during locomotion and horizontal angular VOR gain on both sides <0.8. We classified patients into different groups according to (1) their fulfillment of the Barany guideline for bilateral vestibulopathy (2) the definite etiology of BVP and (3) the four clinical subtypes distributed in our population (recurrent vertigo with BVP, rapidly progressive BVP, slowly progressive BVP, and slowly progressive BVP with ataxia). Medical history of vertigo, hypoacusis or migraine, and family background of imbalance and/or oscillopsia were assessed. Horizontal, posterior, and superior semicircular canal angular VOR gain was registered along with saccadic parameters such as velocity, and dispersion of the saccades' latency values. Results: Barany's Society diagnostic criteria for BVP was accomplished in 89 patients. Among our patients, 13.6% had migraines in their medical history and the idiopathic group accounted for 50% of the population. All four clinical subtypes were found in our population, slowly progressive bilateral vestibulopathy without vertigo was the most frequent one. A percentage of our population could not be categorized into any of the former subtypes, many of these patients were diagnosed with BVP after suffering a single vertigo episode. Lower vHIT gains were found in those patients with Barany's criteria for BVP and oscillopsia was significantly more prevalent in this group. Conclusions: Bilateral vestibulopathy manifests with very different patterns representing a very heterogeneous condition. The distribution of the clinical subtypes and Barany's criteria are a useful clinical tool to differentiate groups of patients. The vHIT can serve as an initial tool for identifying patients with BVP. The finding of bilateral vestibular involvement in a clinically suspected unilateral vestibulopathy should be considered in some patients.